Study of ammonia oxidation with ozone addition - Jie Jian; Hamid Hashemi; Hao Wu; Peter Glarborg (Applications in Energy and Combustion Science, 2023)
The effect of O3 addition on NH3 oxidation was investigated experimentally and through chemical kinetic modeling. Experiments were conducted in a laminar flow reactor at atmospheric pressure and temperatures in the range 225–1000 °C. A detailed reaction mechanism for the NH3-O2-O3 system was developed, and modeling predictions were compared to the flow reactor data. Interpretation of the experimental results was complicated by the formation of ammonium nitrate in the low-temperature inlet and outlet sections of the reactor setup. However, results showed that ammonia oxidation is promoted in the presence of ozone, at the cost of increased formation of nitric oxide and nitrous oxide. Considering the experimental uncertainty, the kinetic modeling was in satisfactory agreement with experiment. The reactivity of the system was controlled by the competition between thermal dissociation of O3 (promoting) and reactions of O3 with the radical pool (inhibiting). A key step was NH2 + O3, which presumably forms H2NO + O2 and serves as a terminating reaction. Modeling predictions under realistic conditions in large 2-stroke diesel engines indicate that the levels of O3 required to obtain sufficiently fast ignition of NH3/air/O3 mixtures are prohibitively large.